Research and technology agreements in the Norwegian concession system of the 1970s - 1990s - Vorobyov, Alexey (Baltic Region, 2013)
This article is devoted to research and technology agreements in Norway, and their positive impact on the development of relations with foreign oil and gas companies during the period of formation of the Norwegian oil and gas industry. Based on archival documents, the article considers Norway’s experience of conclusion of research and technology agreements for transferring the latest technologies of exploration and oil and gas production to national oil and gas companies in the process of developing the country’s oil and gas industry. The author concludes that Norway made significant scientific and technological progress through promoting active cooperation with foreign companies. Norway’s successful experience could be applied by Russian state authorities in order to develop relations with foreign oil companies. These companies could take part in offshore exploration in the Russian sector of the Barents Sea through concluding similar agreements between Russian state institutions, and foreign oil and gas companies, which would give an impetus to the development of the technological component of Russia’s oil and gas sector. Research and technology agreements have been used by Norwegians with the aim of diversification of the economy and prevention of excessive dependence on the energy sector, which is one of the major challenges faced by Russia.